Socialization of processing plastic waste into ecobricks in Teratak Village, North Batukliang District - Syakirin, Syakirin; Ningrum, Baiq Suci Oktapia; Malinda, Malinda; Ramadhan, Bagus Aji; Sweda, I kadek Wira (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Household waste is the largest waste producer in Indonesia compared to other waste producers, where organic and non-organic waste, organic waste is the most abundant. Household waste management is a major challenge in various regions in Indonesia, in-cluding in Teratak Village, Teratak Village, North Batukliang District, Central Lombok Regency. There are many methods that can be used to process waste, including making ecobricks. Ecobrick is a visionary innovation developed as a plastic waste treatment solution. Taken from the two words eco and brick, it is simply defined as an environmentally friendly brick. Until now, ecobrick has not been widely known by Indonesian people, including the people in Teratak Village. The purpose of this community service is for the communi-ty to be able to produce and use ecobricks from the household organic waste they produce in their own homes without disposing of it in TPS. The method of implementing activities is carried out through the delivery of material and direct practice. This counseling and practice activity was well implemented as seen from the enthusiasm and response of the community in participating in the activity and being active in the practice of making ecobricks.